Risk assessment of human exposure to heavy metals, polycyclic aromatic hydrocarbons, and radionuclides in oil-based drilling cutting residues used for roadbed materials in Chongqing, China - Xiong, Deming; Wang, Chaoqiang (Environmental science and pollution research international, 2021)
Oil-based drilling cutting residues (OBDCRs) contain many kinds of carcinogenic contaminants, such as heavy metal elements, polycyclic aromatic hydrocarbons (PAHs), and natural radioactive materials (NORMs), which are great risks for the environment and human health. This study investigated the chemical composition, the radioactive strength, the heavy metal contents, and the org matter contents in OBDCRs and estimated the health risks due to exposure to heavy metals, PAHs, and radionuclides in OBDCRs used for roadbed materials. From the measurements, it was found that the content values of benzopyrene (a), diphenylanthracene (a, h), and petroleum hydrocarbons exceeded the standard limit. The content values of Cu, Zn, As, and Ni were higher than 50% of the standard limit. If OBDCRs were directly used to make roadbed materials, the total carcinogenic risk values (CR n ) of As, benzoanthracene (a), benzopyrene (a), and dibenzoanthracene (a, h) were all higher than 10 −6 . The average absorbed dose rate was higher than 80 nGy/h. There were greater risks of carcinogenic environment and potential harms to human health. To reduce the health risks, it is necessary to consider the strategy of the utilization of OBDCRs, the working time, and the service life of the recycled OBDCRs and establish a legal standard and liability for the utilization of OBDCRs as solid waste resources.